2020
DOI: 10.1002/aqc.3372
|View full text |Cite
|
Sign up to set email alerts
|

Responses of anuran diversity to wetland characteristics and surrounding landscape in the Southern Andean Yungas, Argentina

Abstract: Modification and loss of natural habitats caused by human activities are among the main drivers of biodiversity decline worldwide. To evaluate how land‐use changes affect species diversity at different spatial scales, amphibians represent an excellent group given that their complex life cycle requires both aquatic and terrestrial habitats. In this study, the influence of wetland characteristics and surrounding landscape features on richness and functional diversity of anurans was investigated in 26 natural wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…The average depth of the open water habitats also emerged as one of the best predictors of amphibian richness and abundance in central Argentina. Wetland depth has been extensively associated with hydroperiods (Wells, 2007; Shulse et al, 2010; Brown et al, 2012), and many authors have pointed out that larger and deeper wetlands typically hold high species richness (Pechmann et al, 2001; Drayer & Richter, 2016; Gonzalez Baffa‐Trasci et al, 2020). In contrast, the present study showed that high values of amphibian diversity were associated with shallow constructed water habitats, with B. pulchella the only species strongly associated with deeper water.…”
Section: Discussionmentioning
confidence: 99%
“…The average depth of the open water habitats also emerged as one of the best predictors of amphibian richness and abundance in central Argentina. Wetland depth has been extensively associated with hydroperiods (Wells, 2007; Shulse et al, 2010; Brown et al, 2012), and many authors have pointed out that larger and deeper wetlands typically hold high species richness (Pechmann et al, 2001; Drayer & Richter, 2016; Gonzalez Baffa‐Trasci et al, 2020). In contrast, the present study showed that high values of amphibian diversity were associated with shallow constructed water habitats, with B. pulchella the only species strongly associated with deeper water.…”
Section: Discussionmentioning
confidence: 99%